A comparative study on the effects of a fluoride-containing amalgam alloy and a conventional amalgam alloy on enamel solubility - Chua, Donnabelle Serena D.; Tayag, Marissa B.; Macasaet, Avelino (Adviser).
On the first and second premolars of the upper and lower arch of the Cat's cavity, Class V cavity preparations were made and restored with a conventional amalgam alloy and a fluoride-containing amalgam alloy (Fluor-alloy). After one month, the teeth were extracted and grounded to powdered form. The pre-weighed powdered enamel were each exposed to 5 cc. of 0.5 M acetate buffer at pH 4.0 for twenty four hours. Enamel solubility was then determined by loss of weight. Results show that the fluoride-containing amalgam alloy causes enamel solubility as compared to a conventional amalgam but the difference is not statistically significant.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Fluorides; Dental amalgam; Enamel solubility